The design and development of Bijak Seni, a teaching and learning module that incorporates computational thinking skills in visual art education for secondary school - HARRINNI MD NOOR; IRMA RAHAYU IBRAHIM (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: This study aimed to investigate the feasibility of implementing CT techniques in a Visual Art Education setting. A teaching and learning module called Bijak Seni (Smart Art) was designed and developed based on the ADDIE Model to incorporate CT elements into the teaching and learning of drawing and painting at the secondary level.Method: Presented in the form of a sketch and workbook, this module was printed in color and A3 size. At each tier, a list of learning goals was also included. Students were given ample space to write and scribble ideas. Experts, educators, and students in the field of Visual Art Education participated in a survey.Findings: Results showed that the application of CT in the Bijak Seni Module helped students understand the requirements of the tasks in the Visual Art Education exam. 95.9% of students agreed that applying the CT process helped them to improve their drawing and painting skills. The module also helped them to identify important requirements of the questions, break down the complexity of the required tasks, analyze the drawings made, develop ideas to define the key requirements of the questions, and select the best media and method to deliver their drawing and painting, to meet the objectives and requirements of the examination questions.Implications/Novel Contribution: Furthermore, the Bijak Seni Module can also be applied in any art classroom at any level to improve the teaching and learning of drawing and painting based on certain given standards or requirements. Introducing CT in teaching and learning will give good implications for current Visual Art Education in the 21st Century, motivating student learning and increasing innovative thinking among visual art education students.